2009
DOI: 10.1111/j.1440-1754.2009.01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of children with otitis media: A survey of Australian Aboriginal Medical Service practitioners

Abstract: Australian AMS practitioners treat OM more aggressively in Aboriginal children, consistent with the Australian Government guidelines, despite half being unaware of them. Opportunities to improve management include increased use of pneumatic otoscopy and tympanometry, and decreased antibiotic usage for OM with effusion and chronic suppurative OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Questions addressed the practitioner's demographics; frequency of managing children with OM; management practices; and the availability and waiting times for audiology, ENT services and hearing‐aid provision. The access question was ‘What is your level of access to these services?’, and the waiting time question was ‘What is your typical waiting time for these services?’ The study methodology, ethics approvals and results for management practices have been described in detail previously 10 …”
Section: Methodsmentioning
confidence: 99%
“…Questions addressed the practitioner's demographics; frequency of managing children with OM; management practices; and the availability and waiting times for audiology, ENT services and hearing‐aid provision. The access question was ‘What is your level of access to these services?’, and the waiting time question was ‘What is your typical waiting time for these services?’ The study methodology, ethics approvals and results for management practices have been described in detail previously 10 …”
Section: Methodsmentioning
confidence: 99%
“…For example, in data sourced from a US insurance company, receipt of psychology therapy by children with attention‐deficit/hyperactivity disorder varied by county from 6.3% to 38.1%, and this variation occurred even across counties with a similar number of psychologists . Use of an otoscope or tympanometry to diagnose otitis media in Aboriginal children was also underutilised …”
Section: Executive Summarymentioning
confidence: 99%
“…8 Use of an otoscope or tympanometry to diagnose otitis media in Aboriginal children was also underutilised. 9 ED care -24 studies; asthma was the most common condition (seven studies), followed by bronchiolitis and fever (four each), pneumonia (three), analgesia/sedation and concussion (two each). Three studies were from Australia.…”
Section: Executive Summarymentioning
confidence: 99%
“…For Aboriginal and Torres Strait Islander children, adherence to guidelines with respect to prescribing antibiotics (97%; OTIT08) was similar to that reported in a 2008 survey of vignette responses by medical practitioners working in Aboriginal Medical Service (92%). 46 The 2008 study found that 25% would treat AOM with courses of longer than 7 days, while our study found only 13% treating for 7 days (OTIT13); we only counted compliance if 50 mg/kg/day of amoxicillin was prescribed as per Australian Health Department recommendations for clinical management of otitis media in Aboriginal and Torres Strait Islander populations. 47 Adherence to treatment guidelines for Aboriginal and Torres Strait Islander children may impact later quality of life for these populations.…”
Section: Comparison With Other Studiesmentioning
confidence: 85%